Forgiveness, personality and gratitude - Felix Neto (2007)
Recent evidence indicates that personality plays a role in the study of forgiveness, but the literature has been limited. This study sought to determine whether gratitude accounted for a significant portion of the variance beyond that of personality in the study of dispositional forgiveness (enduring resentment, sensitivity to circumstances, and overall propensity to forgive). One hundred and fifty-two Portuguese college students (5 1 % females and 49% males, mean = 2 1. 10 years) participated in the study. The results confirmed that personality, particularly agreeableness and neuroticism correlate with enduring resentment and overall tendency to forgive. Additionally, results using multiple regression models indicated that gratitude explained a significant amount of variance of overall propensity to forgive.